Multimodal Texts in Disciplinary Education A Comprehensive Framework - Danielsson, Kristina; Selander, Staffan (Springer International Publishing : Imprint: Springer, 2021)
This open access book provides an introduction to multimodality and the role of multimodal texts in today's education. Presenting a comprehensive framework for analysing and working with multimodal texts in disciplinary education, it serves as a tool for researchers and teachers alike. The second part of the book focuses on sample analyses of a variety of educational texts for different age groups and from different disciplines, including games and online resources. The authors also comment on the specific challenges of each text, and how teachers can discuss such texts with their students to enhance both their understanding of the content and their multimodal literacy. The book is intended for researchers in fields like education and multimodal studies, and for teacher educators, regardless of school subject or age group. With the combined perspectives on text analysis and implications for education, the book addresses the needs of teachers who want to work with multimodalaspects of texts in education in informed ways, but lack the right tools for such work. .